Ability to Participate in Social Activities of Rheumatoid Arthritis Patients Compared with Other Rheumatic Diseases: A Cross-Sectional Observational Study - Laura Cano-García; Natalia Mena-Vázquez; Sara Manrique-Arija; Rocío Redondo-Rodriguez; Carmen María Romero-Barco; Antonio Fernández-Nebro (Diagnostics, 2021)
Objectives: To compare the ability to participate in social activities among rheumatoid arthritis patients with other rheumatic disease patients and identify potentially implicated factors. Patients and methods: Between June and November 2019, we consecutively selected patients aged ≥18 years with RA (defined according to ACR/EULAR 2010), SpA (ASAS/EULAR 2010), and SLE (ACR 1997). Main outcome measures: Ability to participate in social roles and activities evaluated using the PROMIS score v2.0 short-form 8a (PROMIS-APS). Secondary outcomes: Participation in social activities according to a series of variables (mobility, depression, satisfaction with social relationships, social isolation, company, emotional support, instrumental support, and support via information). We evaluated the association between the ability to participate in social activities and associated variables using multivariable linear regression analysis. Results: The study population comprised 50 patients with RA (33.1%), 51 patients (33.8%) with SpA, and 50 patients (33.1%) with SLE. The mean PROMIS-APS scores were similar in the three groups. The multivariable analysis for the whole sample showed that the ability to participate in social activities was inversely associated with depression and directly with social satisfaction, mobility, company, and age. The stratified analysis revealed an inverse association between inflammatory activity and ability to participate in social activities in patients with RA and SpA, but not in those with SLE. Conclusion: All patients with RA, SpA, and SLE had a similar ability to participate in social activities. This was associated with other psychosocial factors (social satisfaction, mobility, company, depression) and clinical factors (age and inflammatory activity).